Navigating the digital landscape : understanding customer behaviour in the online world - Singh, Nripendra; Kansra, Pooja, 1984-; Gupta, S. L. (Emerald Publishing Limited, 2024)
Rapid digitalisation and social media use has led to the evolution of customer behaviour and for any business it has become imperative to understand customer behaviour in the digital world - the chapter authors in Navigating the Digital Landscape explore a wide range of topics to help the reader harness the positive aspects of digital commerce and mitigate risks. The chapters look at artificial Intelligence and augmented reality, trend setting and the impact of social media, the effect of the COVID-19 pandemic on various sectors, and much more. Readers will learn service quality, peer pressure, online reviewers' effect in the digital environment to aid in understanding the various risks and challenges involved in the digital environment, with examples of changing business and consumer scenario case studies as a result of Digital Transformation.
Keywords: Electronic commerce.; Business enterprises -- Technological innovations.; Technological innovations -- Social aspects.; Business & Economics -- E-Commerce -- General.; E-commerce: business aspects.; elektronické knihy; electronic books